Graphene-based phase change composites for energy harvesting and storage: State of the art and future prospects. (July 2019) - Allahbakhsh, Ahmad; Arjmand, Mohammad
Abstract: Among different techniques for the storage and release of energy, phase change materials hold great promise to satisfy the growing needs of smart thermal energy management and portable thermal energy sectors. However, low thermal conductivity and shape-instability through the phase transition process are two main drawbacks of phase change materials towards industrialization. In this review paper, recent progresses in employing graphene-based nanostructures as a versatile solution for the aforementioned shortcomings are presented in detail. Graphene-based nanostructures, as either graphene nanosheets or graphene-based porous nanostructures, can improve the thermal conductivity of phase change materials and shape stability of these energy storage systems significantly. Moreover, recent studies presented here suggest that graphene-based phase change composites can be considered as promising energy harvesting systems for solar-to-thermal and solar-to-electrical energy conversion and storage applications. Graphical abstract: Image 105048